Default options and training participation - Lex Borghans; Bart H. H. Golsteyn (Institute for the Study of Labor (IZA), 2013)
This paper analyzes whether defaults affect the choice for courses followed at work. In addition, we analyze whether the size of the default effect varies with employees' personality and skill-deficiencies. We perform an experiment in which workers are hypothetically offered three courses which they can accept or exchange for other courses. Randomizing the default package of courses, we identify the default effect. Default courses are chosen approximately three times more often than other courses. They are chosen more often if people have skill-deficiencies in these courses, suggesting that people consider the default to be an advice. Women choose default courses more often than men. Women with less self-confidence and men with lower cognitive skills choose the default courses more often.
Keywords: J24; J31; I2; 330; human capital investment; training; default